Students' and teachers' perceptions of the use of mobile technology in university preparation classes : a thesis presented in partial fulfilment of the requirements for the degree of Master in Applied Linguistics at Massey University, Manawatu Campus, New Zealand - Aldrich, Susanne Thelma (Massey University, 2017)
As in many aspects of society today, mobile technology has a presence in educational arenas. This study investigates and compares the views and perceptions of teachers and students about the appropriate use of mobile technology in university preparation classes, how the presence of mobile technology influences the classroom environment, and about what students and teachers believe to be their respective roles in the regulation of the use of mobile technology. To investigate this the following instruments were used: a student survey to gather quantitative data about their beliefs about mobile technology in class, their behaviour around devices, and their expectations of teaching practices and regulation of devices; student focus groups using four teacher scenarios (describing different teacher behaviour and attitudes) as a basis for the discussion; and teacher focus groups posing questions gleaned from the results of the student survey and focus groups. The overall objective was to determine if any gaps in perceptions, attitudes and expectations existed between students and teachers. Both parties agreed that devices were useful educational tools to use in class. However, there were opposing viewpoints about personal use of devices. Students expected teachers to take responsibility for regulating student behaviour around the use of devices, while teachers sought to prepare students to take personal responsibility and become autonomous learners. A need for establishing etiquette in the classroom was recognised. Teachers acknowledged that although students were skilled users of mobile technology, they lacked vital computer skills. Overall, there was a discrepancy between student and teacher beliefs about philosophical responsibility, the scope of technical ability, and logistical possibilities in the classroom. To conclude, the study confirmed that the nature of the classroom had changed and that all stakeholders need to be cognisant about everchanging technology.
Keywords: Mobile communication systems in education; College preparation programs; English language; Study and teaching; Foreign speakers; Aids and devices